Synthesized 18-Lead Electrocardiogram in Diagnosing Posterior Stemi-Equivalent Acute Coronary Syndrome in Patients with NSTEMI - Tomoki Horie; Rikuta Hamaya; Tomoyo Sugiyama; Hidenori Hirano; Masahiro Hoshino; Yoshihisa Kanaji; Tetsumin Lee; Taishi Yonetsu; Tetsuo Sasano; Tsunekazu Kakuta (Cardiology Research and Practice)
Objective. To assess the clinical utility of synthesized V7–V9 ST-segment elevation (sV7-9 STE) in patients with 12-lead-electrocardiogram (ECG)-based non-STE myocardial infarction (NSTEMI) in diagnosing left circumflex artery (LCx) STEMI-equivalent acute coronary syndrome (ACS). Background. The 12-lead-ECG is insufficient for diagnosing patients with ACS, especially those with an LCx culprit. Methods. We retrospectively examined 219 patients with NSTEMI who underwent synthesized 18-lead ECG acquisition on admission and urgent catheterization. Associations between baseline variables, including sV7-9 STE and LCx STEMI-equivalent ACS, were analyzed using logistic regression models and receiver operating characteristics. LCx-culprit ACS was defined as thrombolysis in myocardial infarction (TIMI) 0–1 flow. The association between sV7-9 STE and myocardial damage was also assessed. Results. The mean (SD) age of the population was 68.8 (12.0) years, and 81.7% were men. LCx-culprit NSTEMI occurred in 58 (26.5%) patients and 15 (6.8%) were LCx STEMI-equivalent. SV7-9 STE was observed in 16 patients (7.9%). SV7-9 STE was the sole significant predictor of LCx STEMI-equivalent ACS with an odds ratio of 19.0 (95% CI: 5.6–63.9, p<0.001), area under the curve of 0.71 (95% CI: 0.58–0.84), sensitivity of 46.7%, and specificity of 95.6%. After adjustment for confounders, sV7-9 STE was significantly associated with a 308% (95% CI: 78–834%) increase in peak high-sensitivity cardiac troponin I (p=0.001). Conclusions. SV7-9 STE had sole preprocedural diagnostic utility in detecting LCx STEMI-equivalent ACS with greater myocardial damage among patients with 12 ECG-based NSTEMI. The use of synthesized extra leads on admission may help identify patients with NSTEMI requiring primary revascularization.